2007
DOI: 10.1111/j.1467-8411.2007.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Financing Health Insurance in Asia Pacific Countries

Abstract: The paper discusses models of health insurance, including compulsory (social) health insurance, voluntary insurance, and community-based financing schemes. It illustrates the features of these models in terms of coverage, funding, sustainability, payment mechanisms, public-private mix, risk protection, and cost-containment properties, and outlines some emerging challenges to health financing arrangements. Health financing systems used in Japan, Korea, Taiwan, ASEAN and China are discussed, and implications are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Health insurance schemes undertake various initiatives to reach the vulnerable segments of the populations, such as discount cards, exemption schemes or free enrolment for vulnerable populations. For example, targeted policies of the National Health Insurance Program in the Philippines [32][33][34] and the Thai universal coverage scheme 34 increased the number of insured indigents and poor. In other countries, social inclusion is not achieved to the same extent, and in Cameroon, 35 …”
Section: Impact Of Health Insurancementioning
confidence: 99%
“…Health insurance schemes undertake various initiatives to reach the vulnerable segments of the populations, such as discount cards, exemption schemes or free enrolment for vulnerable populations. For example, targeted policies of the National Health Insurance Program in the Philippines [32][33][34] and the Thai universal coverage scheme 34 increased the number of insured indigents and poor. In other countries, social inclusion is not achieved to the same extent, and in Cameroon, 35 …”
Section: Impact Of Health Insurancementioning
confidence: 99%
“…This finding is precious because it indicates that the Iranian health system suffers from ineffective referral and payment system policies and has failed to control consumer demand. As long as there is no mandatory referral system, cost-containment policies will be limited [16] . Besides, the fee-for-service payment system creates a much-desired condition for ex-post moral hazard by providing high access to all health system levels [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed the increasing impact of moral hazard on health care expenditures, especially in health systems that work with fee-for-service payment models [14] , [15] and those without a mandatory referral system [16] , [17] . The presence of these two determinant factors and high medical insurance population coverage (about 95%) in Iran [18] , seems to have provided the appropriate conditions for the ex-post moral hazard problem.…”
Section: Introductionmentioning
confidence: 99%